VD_FINDINFO HC / 2011 / 683 vom 12. Dezember 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, CONDITION DE RECEVABILITÉ | 176 al. 1 CC, 310 CPC (CH), 317 al. 1 CPC (CH), 317 al. 2 CPC (CH)